Dysregulation of MiR-21, MiR-221 and MiR-451 During Neoadjuvant Treatment of Breast Cancer: A Prospective Study - Carine Bispo Patury; Brenda Luanny Maia Santos; Anna Lucia Carvalho Matos; José Slabi; Luciene Cristina Campos Gastalho; Carla Martins Kaneto (Biomolecules)
Background: Breast cancer is highly heterogeneous disease in which different responses are observed to the same treatment for different subtypes and extents of similar diseases. Considering this scenario, the search for tumor biomarkers is indispensable, with current evidence suggesting that circulating microRNAs are viable biomarkers. This study evaluated the expression of miR-21, miR-221, miR-195, and miR-451 in patients with breast cancer undergoing neoadjuvant treatment at oncology outpatient facilities in Brazil. Methods: We conducted a prospective and observational study in which blood samples were collected for microRNA expression analysis, comparing control and breast cancer patients who were candidates for neoadjuvant treatment groups. The expression of microRNAs was investigated by qRT-PCR method. For parametric data analysis, one-way ANOVA with Tukey’s post hoc test was used. Results: Thirty-three participants (all female) were included in the control group and twenty-seven participants were included in the study group. The non-special subtype of breast cancer was found in 96% of the study group participants; 88.9% were locally advanced tumors (T3, T4), 40.7% were luminal tumors, 33.3% were HER-2-positive, and 26% were triple negative tumors. Expression analysis of microRNAs during neoadjuvant treatment, using miR-16 as a normalizer, showed higher expression levels of miR-21 and miR-221 at the end of treatment, and high expression levels for miR-451 were also observed at the beginning of treatment. Conclusion: This is the first study that evaluates the expression of microRNAs in the context of neoadjuvant treatment of breast cancer in the Brazilian population. Our results suggest that there is a deregulation of miR-21, miR-221, and miR-451 during neoadjuvant treatment in these patients.